Fenomena Fonologis Qiraat al-Yazidi dan implikasinya dalam Penafsiran - Wafiudin, M. Afif; Fadhil Achmad Agus Bahari (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The method or way of reading the Qur'an literally is very varied, so that is why a discipline of qiraat was born to systematise it. This difference in reading method often leads to differences in the interpretation of the verse. Al-Yazidi, as one of the muqri‘, has three major discussions namely phonological, lexical, and grammatical aspects in the recitation he narrated. This research will focus on the character of Al-Yazidis reading, its implications for interpretation, and where he took the route of narrating his reading. This research is a library research and uses descriptive-analytical method. This study argues that the differences in interpretation that arise in Al-Yazīdī’s qiraat come from differences in word origin and differences in sound. Differences in word origin that result in differences in sound essentially have an influence on interpretation, while differences in sound do not all have implications for determining meaning. This research also found a unique fact that Al-Yazīdī once narrated a reading not from a muqri‘ as muqri‘ in general. But this, after being investigated, did not cause problems and undermine Al-Yazīdī's credibility as a reader of the Qur'an.